(3GdYHGH aj TQM GddHGHs - (3LeGd GdOjf YHO Gddg Hf eMeO Hf CMeO GdMSjfj GdfjSGHhQj GdeYQha HGdfbQg cGQs; (3GdGSaQGjjfj , eMeO Hf eMeO Hf CMeO, JGL GdOjf,J (B684 (3g` s ((3eMeO Hf CHj HcQ Hf Ydj GdMSfj GdCSjhWj s)
(3ChdgG (B:s
(3hHYO, aEf cJGH GddHGH aj Yde GdEYQGH, deG cGf cJGHkG UMjMkG eYGfjg s
(3BNQgG (B:s
(3hGNJUGU GdLRe HGdaYd hEP bO hajfG HeG hYOfG ef Jhajg GdCbSGe GdCQHYI efgG adfNJe GdcJGH, s
(3HChdgG Jedc eDQN SfI (B855(3g`s
(3hHgG fXGe GdJYbjHIs
(3CKQ WeSs
(3dH GdGdHGH ai Yde GdEYQGH GdeSei HGddHGH ai GdfMh s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdfMhs